Calmodulin mutations and life-threatening cardiac arrhythmias: insights from the International Calmodulinopathy Registry. (6th June 2019) - Crotti, Lia; Spazzolini, Carla; Tester, David J; Ghidoni, Alice; Baruteau, Alban-Elouen; Beckmann, Britt-Maria; Behr, Elijah R; Bennett, Jeffrey S; Bezzina, Connie R; Bhuiyan, Zahurul A; Celiker, Alpay; Cerrone, Marina; et al.
Abstract: Aims: Calmodulinopathies are rare life-threatening arrhythmia syndromes which affect mostly young individuals and are, caused by mutations in any of the three genes ( CALM 1–3 ) that encode identical calmodulin proteins. We established the International Calmodulinopathy Registry (ICalmR) to understand the natural history, clinical features, and response to therapy of patients with a CALM -mediated arrhythmia syndrome. Methods and results: A dedicated Case Report File was created to collect demographic, clinical, and genetic information. ICalmR has enrolled 74 subjects, with a variant in the CALM1 ( n  = 36), CALM2 ( n  = 23), or CALM3 ( n  = 15) genes. Sixty-four (86.5%) were symptomatic and the 10-year cumulative mortality was 27%. The two prevalent phenotypes are long QT syndrome (LQTS; CALM -LQTS, n  = 36, 49%) and catecholaminergic polymorphic ventricular tachycardia (CPVT; CALM -CPVT, n  = 21, 28%). CALM -LQTS patients have extremely prolonged QTc intervals (594 ± 73 ms), high prevalence (78%) of life-threatening arrhythmias with median age at onset of 1.5 years [interquartile range (IQR) 0.1–5.5 years] and poor response to therapies. Most electrocardiograms (ECGs) show late onset peaked T waves. All CALM -CPVT patients were symptomatic with median age of onset of 6.0 years (IQR 3.0–8.5 years). Basal ECG frequently shows prominent U waves. Other CALM -related phenotypes are idiopathic ventricular fibrillation (IVF, n  = 7), sudden unexplained death (SUD, n  = 4), overlapping features of CPVT/LQTS ( n  = 3), and predominant neurological phenotype ( n  = 1). Cardiac structural abnormalities and neurological features were present in 18 and 13 patients, respectively. Conclusion: Calmodulinopathies are largely characterized by adrenergically-induced life-threatening arrhythmias. Available therapies are disquietingly insufficient, especially in CALM -LQTS. Combination therapy with drugs, sympathectomy, and devices should be considered.